2018
DOI: 10.1371/journal.pone.0191676
|View full text |Cite
|
Sign up to set email alerts
|

Broad adsorption of sepsis-related PAMP and DAMP molecules, mycotoxins, and cytokines from whole blood using CytoSorb® sorbent porous polymer beads

Abstract: ObjectiveSepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. In sepsis and septic shock, pathogen-associated molecular pattern molecules (PAMPS), such as bacterial exotoxins, cause direct cellular damage and/or trigger an immune response in the host often leading to excessive cytokine production, a maladaptive systemic inflammatory response syndrome response (SIRS), and tissue damage that releases DAMPs, such as activated complement and HMGB-1, into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 54 publications
3
137
0
7
Order By: Relevance
“…The source of the infection can lead to an uncontrollable inammatory cascade; due to continuity differences, its effects are different to human pathogenesis. [16][17][18] In addition, due to different operating intensities it is difficult to standardize for comparison among diverse groups, and so this experiment did not use the CLP model. Although the bacterial infusion or instillation model is easy to operate, the model is greatly affected by bacterial species, inoculum size, susceptible sites and infection routes leading to poor stability.…”
Section: Discussionmentioning
confidence: 99%
“…The source of the infection can lead to an uncontrollable inammatory cascade; due to continuity differences, its effects are different to human pathogenesis. [16][17][18] In addition, due to different operating intensities it is difficult to standardize for comparison among diverse groups, and so this experiment did not use the CLP model. Although the bacterial infusion or instillation model is easy to operate, the model is greatly affected by bacterial species, inoculum size, susceptible sites and infection routes leading to poor stability.…”
Section: Discussionmentioning
confidence: 99%
“…The CytoSorb ® technology (CytoSorbents, Monmouth Junction, NJ, USA) is an hemoperfusion cartridge filled with polymer beads that can adsorb pro-and antiinflammatory mediators, but not endotoxins [41]. In vitro experiments have shown removal rates of cytokines > 90-95% [42].…”
Section: Removing Cytokinesmentioning
confidence: 99%
“…Particles outside this size range, including larger immune cells and smaller serum electrolytes recirculate unchanged. While the manufacturer states that bacterial endotoxins are not removed with CytoSorb, a study has shown some efficacy in removing toxins within the 5-60 kDa range [92].…”
Section: History Of Cytokine Adsorption Therapymentioning
confidence: 99%